Primitive neuroectodermal tumor of the uterus: Excellent clinical response following a multimodal treatment approach - Adam Khorasanchi; Elizabeth Kertowidjojo; Sara Kim; William Burke; Andrzej Kudelka (Elsevier, 2020)
We present a case report of a patient with uterine primitive neuroectodermal tumor (PNET). The patient underwent surgical management followed by pelvic radiation and intravaginal brachytherapy. Following a stable interval, the patient was found to have new onset spinal, pulmonary, and adrenal metastatic disease. She was subsequently started on high dose carboplatin and etoposide. An interval reduction of her metastatic disease was observed after three cycles. We conclude that a multimodal approach, including platinum-based adjuvant chemotherapy with etoposide, can be effective in patients who present with residual or recurrent disease after surgical and radiation therapy. However, more robust studies with longer follow-up periods will be needed to establish a consensus regarding effective treatment options.